Phenotypic characterization of mutants in vaccinia virus gene G2R, a putative transcription elongation factor. - Black, E P (1996)
The phenotypic defects of two mutants of vaccinia virus, the lesions of which map to gene G2R, were characterized in vivo, and the results suggest a role for the G2R protein in viral transcription elongation. Both a temperature-sensitive mutant, Cts56, and an isatin-beta-thiosemicarbazone-dependent deletion mutant, G2A, in gene G2R have a characteristic and unique defect in late viral gene expression. The G2R mutants synthesize early viral RNA, early viral proteins, and viral DNA normally under nonpermissive conditions. In G2R mutants, late viral protein synthesis begins at the normal time, low-molecular-weight viral proteins are synthesized in normal quantities, but synthesis of high-molecular-weight viral proteins is reduced in amount. Intermediate and late promoter utilization is normal in G2R mutants, but intermediate and late RNAs are reduced in size. The reduction in length of the intermediate and late mRNAs represents a truncation of mRNA 3' ends. Thus, intermediate and late RNAs are too short to encode large proteins but long enough to encode small proteins, therefore accounting for the protein synthesis phenotype. These results suggest that the G2R protein acts to regulate the elongation potential of the viral RNA polymerase late during a vaccinia virus infection.